A Cross-Sectional Evaluation of Cigarette Smoking in the Brazilian Youth Population - Brito, Emerson Silveira; Bessel, Marina; Dornelles, Thayane; Moreno, Flávia; Pereira, Gerson; Da Ros Wendland, Eliana Márcia (Frontiers in Public Health, 2021)
Introduction: The transition from adolescence to adulthood involves a variety of physical, behavioral, and social transformations, often including tobacco use. Because understanding smoking at this stage is important for tobacco control, we aimed to analyze the prevalence of cigarette smoking in the Brazilian youth population. Methods: This study included participants aged 16 to 25 years from all Brazilian capitals. A standardized questionnaire was administered by trained healthcare professionals to collect information about sociodemographic status, sexual behavior, and tobacco use. The samples from each capital were weighted by age range and sex. Results: Of the 8,581 participants, 15.1% were current smokers, and 20.0% were former smokers; the average age at first tobacco use was 15.5 years. The prevalence of smoking in men was higher than that in women (20.1% vs. 10.3%, p<0.01). Education level was associated with current smoking and former smoking. Participants with an elementary education level had a higher smoking prevalence (PR 5.84 95% CI 4.29-7.95) than those with a secondary education (PR 2.19 95% CI 1.63-2.93) and those with higher education. Those without current partners (PR 1.27 95% CI 1.03-1.56) also had a higher prevalence of smoking than those with partners, and participants who had a previous same-sex sexual experience smoked more (PR 2.29 95% CI 1.78-2.96) than those who did not. In addition, regular use of alcohol was associated with higher prevalence of cigarette smoking (PR 5.65 85% CI 4.03-7.90) than a lack of alcohol consumption. Skin color and socioeconomic class did not exhibit significant relationships with tobacco use patterns. Conclusions: Smoking was associated with education level regardless of social class, and some specific behaviors associated with a same-sex sexual experience were associated with a higher prevalence of smoking. These findings are important for formulating policies and directing actions to combat and prevent smoking among young populations.